User experience of body gesture interaction in mobile gaming / Nabila Huda Nasrudin - Nasrudin, Nabila Huda (2010)
The title of this study is User Experience of Body Gesture Interaction in Mobile Gaming where mobile nowadays caused the changing of the way people use mobile phone dramatically. More sensors devices can transform the mobile user experience by allowing control through gestures and other types of movement. Currently most mobile phones provide interactions through keypad, standard keys board or joystick. Hence, the user can play the game by using the joystick or standard keys board rather than body gesture interaction known as virtual environment. There are a lot of studies covered the interaction techniques but not on the user experience of body gesture interaction in mobile gaming. The objectives of this study are to identify the types of interaction styles of body gesture in mobile gaming, to investigate user experiences towards interaction style of body gesture interaction gaming and to identify the limitations of body gesture interaction in mobile game application. Application domain in this study is on mobile phone. Significance of this study is for the designer, provider and users of mobile phone. This study consists of four phases which are research planning, concept findings, empirical study and documentation. The types of interaction styles on body gesture gaming are walking, running, jumping, turning, ducking and swing hands. The experiment has been conducted among eight participants and they have required playing four of body gesture interaction gaming by Sony Ericsson Yari. Their user experience indicates that body gesture interaction in mobile gaming are good for health, more fun, learnability, more active and real-world environment. However, body gesture interaction in mobile gaming has several limitations such as embarrassed, required spaces for movement, aggressive motion and single player. The study has been concluded by summarizing the work and suggested recommendation for future work.